Strategy to Increase Consumer Trust in Affiliate Links on Social Media - Piliana, Ni Putu Christina; Maradona, Agus Fredy (Quantitative Economics and Management Studies, 2024)
Affiliate marketing in Indonesia has experienced significant growth, especially with the development of the e-commerce & e-marketplace industry. Affiliate marketing is a performance-based model where content creators (affiliators) earn commissions by promoting products or services through links, and affiliates earn a share of revenue from users who make purchases through those links. This is a win-win solution for creators and brands. In this context, building consumer trust is the most important thing. This research aims to analyze strategies to increase consumer trust in affiliate links on social media. This research took samples from active social media users who had or had experience shopping via affiliate links on social media, with gender, age, latest education as respondent characteristics and product type, type of social media, and consumer characteristics as control variables. This research is quantitative research using a purposive sampling method. This research aims to explore effective strategies for increasing consumer trust in affiliate links on social media. This study uses the Structural Equation Modeling Partial Least Squares (SEM PLS) method with the help of SmartPLS 4 software to analyze the data samples obtained. The research results show that factors such as information transparency, affiliate reputation, product and service quality, content relevance, and user experience have a significant effect on consumer trust. However, it was found that consumer attitudes did not significantly moderate the influence of product and service quality and user experience on consumer trust. These findings help marketing practitioners create better strategies to foster consumer trust in affiliate links in the digital era.